Women's right to Islam (Journal of the College of Basic Education, 2024)
Before Islam, women were deprived of their rights and were given birth as infants who had not seen anything of the light of the world yet. When Islam came, it protected women, raised their status and status, preserved their rights, and recommended that they be treated gently and kindly, voluntarily, at a time when women lived during the period that preceded the Islamic message. Tragic conditions, and they consider female birth to be an abomination, so female infanticide was widespread. However, in the period after the Islamic message, especially in the time of the Prophet Muhammad (peace be upon him), she had the right to freedom of marriage and to choose a husband, and it was not permissible to force her to marry a man she did not want, and she also had an important role. As she contributed alongside men in building the Islamic state by performing different and diverse roles, and for this reason Islam gave women their full rights that had been robbed of them in previous religions and in people’s beliefs.